Estimation of radiological and functional outcome of closed calcaneus fractures treated by open reduction internal fixation with calcaneal plate and screws: A prospective study - Sarkar, Pranjal; Indrajit Saha,; Surojit Mondal,; Susanta Rakshit,; Bandyopadhyay, Ranadeb; Saha, Debasish (Asian Journal of Medical Sciences, 2023)
Background: Calcaneus fracture comprising only about 2% of all fractures is the most common tarsal bone fracture, constituting about 60% of all tarsal bone fractures. Most of calcaneus fractures are intra-articular making them difficult to treat conservatively with unpredictable outcome. With surgical fixation, there is apprehension of soft-tissue complication. Hence, we decided to conduct this study to estimate radiological and functional outcome of closed calcaneus fractures treated by open reduction internal fixation (ORIF) with calcaneal plate and screws. Aims and Objectives: Study was conducted to estimate radiological and functional outcomes of closed calcaneus fractures treated by ORIF with calcaneal plate and screws. Materials and Methods: This prospective study included patients with calcaneus fractures operated by extended lateral approach and fixed by ORIF with standard calcaneal low-profile locking plates and screws at Bankura Sammilani Medical College, Department of Orthopaedics and reviewed at out or inpatient department between January 2021 and August 2022. 15 patients with total 19 calcaneus fractures, with 4 patients needing bilateral calcaneus fixation, were enrolled for the study. The data were then recorded as for duration to fracture union, satisfactory radiological reduction as for Bohler’s angle, and functional outcome using the American Orthopaedic Foot and Ankle Society score. Data were then processed and analyzed with the help of Microsoft Excel spreadsheet and SPSS (version 27.0) using descriptive statistics in terms percentage and frequency, range, and standard deviation. Results: Comparing pre-operative and post-operative Bohler’s angle, 17 (89.47%) had adequate reduction and for 2 (10.53%) cases, adequate reduction could not be achieved. In our study, overall 7 out of 19 limbs (36.84%) had excellent functional outcome, 10 (52.63%) had good result, and 2 (10.53%) had fair result. Conclusion: ORIF of displaced intra-articular calcaneal fractures through extended lateral approach with low-profile locking calcaneal plates gives good subtalar joint reduction in most cases with satisfactory functional outcome with few complications.